2004
DOI: 10.1124/dmd.104.000885
|View full text |Cite
|
Sign up to set email alerts
|

High Absorption but Very Low Bioavailability of Oral Resveratrol in Humans

Abstract: ABSTRACT:The dietary polyphenol resveratrol has been shown to have chemopreventive activity against cardiovascular disease and a variety of cancers in model systems, but it is not clear whether the drug reaches the proposed sites of action in vivo after oral ingestion, especially in humans. In this study, we examined the absorption, bioavailability, and metabolism of 14 C-resveratrol after oral and i.v.doses in six human volunteers. The absorption of a dietary relevant 25-mg oral dose was at least 70%, with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
1,370
2
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,577 publications
(1,478 citation statements)
references
References 18 publications
41
1,370
2
18
Order By: Relevance
“…13 Moreover, several reports showed that resveratrol could prevent or delay the onset of cancer. [49][50][51][52] These effects are observed despite extremely low bioavailability and rapid clearance from the circulation, 53 which explains why many laboratories develop resveratrol-derivatives with better in vivo efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, several reports showed that resveratrol could prevent or delay the onset of cancer. [49][50][51][52] These effects are observed despite extremely low bioavailability and rapid clearance from the circulation, 53 which explains why many laboratories develop resveratrol-derivatives with better in vivo efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A rápida conjugação com sulfato no intestino e fígado foi responsável pela baixa biodisponibilidade oral do resveratrol. 20,21 Outros fatores que limitam o aproveitamento terapêutico do resveratrol incluem a sua baixa estabilidade frente à oxidação e baixa solubilidade aquosa. 22 Inúmeros estudos relatam os benefícios do resveratrol sobre a pele, fazendo com que a liberação tópica deste composto constitua uma interessante alternativa à administração oral para o tratamento de várias desordens cutâneas.…”
Section: Introductionunclassified
“…Entretanto, a maioria deles tem sido focada em determinações simultâneas de vários compostos do vinho 2,35,36 e identificação de metabólitos do resveratrol em plasma humano e animal. 20,37,38 Assim, este trabalho também descreve o desenvolvimento e validação de um método de cromatografia líquida de alta eficiência para a determinação do resveratrol nas suspensões coloidais e nos hidrogeis obtidos após a incorporação da hidroxietilcelulose.…”
Section: Introductionunclassified
“…Resveratrol forms extensive conjugated metabolites including glucuronides, sulfates and methylated products (25 -27) . Pharmacokinetic studies on acute resveratrol doses indicate significant distribution thereof to the kidneys (27,28) , with rapid excretion in urine (25,27,29) . These metabolites are capable of crossing glomerular membranes and accumulating in the kidney tubules where they may act as pro-oxidants or activate oxidative stress, as seen for various polyphenolic conjugates (27,30) .…”
Section: Inflammationmentioning
confidence: 99%